THE EFFECT OF STORE ATMOSPHERE, PRICE, AND LOCATION TOWARDS PURCHASE DECISION (STUDY ON ROKETTO COFFEE & CO MALANG) - Elam Redondo (Jurnal Ilmiah Mahasiswa FEB, 2020)
This research aims to discover the impact of Roketto Coffee & Co Store Atmosphere, Price and Location towards Purchase Decision with the study among Roketto Coffee & Co consumers in Malang. This explanatory research explains the relationship and the influence between one variable and another through hypothesis testing. This research collected sample of 140 respondents via online survey. The sample of this research consists of the respondents who are familiar and recognized Roketto Coffee & Co Malang's existence. The data analysis used in this research was the Multiple Linear Regression Analysis. From the results of testing three hypotheses, it can be concluded that the variable of Store Atmosphere, Price, and Location have a significant influence on the Purchase Decision. This research implied that proper maintenance of the Store Atmosphere, Price, and Location of Roketto Coffee & Co Malang would increase their consumers' purchase decision.Keywords: Store Atmosphere, Price, Location, Purchase Decision